An in vivo study on the sealing efficacy of a pit and fissure sealant - Lapasaran, Ma. Sirikit G.
This in vivo study intents to determine the sealing efficacy of a pit and fissure sealant. Twenty-four upper and lower deciduous posterior teeth of two monkeys were used for the study. Twenty teeth were applied with sealant and four were used as the control group. These teeth were then subjected to dye penetration for twelve hours, then sectional buccolingually and analyzed for the presence or absence of dye penetration. Analysis of the results with the use of a dissecting microscope show that the teeth previously applied with sealant have been completely filled but these teeth have been penetrated by the dye which mean there is leakage present and so the sealing efficacy of the sealant is rather questionable.